Improving the Effectiveness of Public Services through Technology-Based Service Innovations in Indonesia - Nugroho Widianto (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This study aimed to investigate the role of technology-based service innovations in improving the effectiveness of public services in Indonesia. The background of this study is based on the increasing demand for public services and the need for more efficient and effective service delivery methods. The study adopted a qualitative research method, including interviews and focus group discussions with key stakeholders involved in the delivery of public services. The findings of this study suggest that the implementation of technology-based service innovations can improve the effectiveness of public services by increasing accessibility, speed, and accuracy of service delivery. The study recommends that policymakers and public service providers should invest in technology-based innovations to improve the quality of public services and enhance the overall customer experience.